2007
DOI: 10.1063/1.2512700
|View full text |Cite
|
Sign up to set email alerts
|

A molecular dynamics model for the interaction of energetic ions with SiOCH low-κ dielectric

Abstract: A molecular dynamics model is used to investigate the interaction of energetic ions with fluorocarbon passivated Si, O, C, and H (SiOCH) based low-κ dielectrics. The model includes a set of interatomic potentials required for the SiOCH–CFx interaction system, where the two- and three-body pseudopotentials have either been obtained from published literature or computed using ab initio techniques. The test structure used for the ion interaction simulations is put together through deposition of low energy SiOx+, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The question of film formation, surface modification and etching was addressed by Kawase and Hamaguchi [2007] A similar study was reported by Smirnov et al [2007] for an important low dielectric constant ('low-κ') material, containing Si, C, O and H ('SiCOH'). These authors found that a FC passivation layer forms in the near-surface region when impacting their model dielectric film with CF x ions.…”
Section: Ion-assisted Etchingmentioning
confidence: 85%
“…The question of film formation, surface modification and etching was addressed by Kawase and Hamaguchi [2007] A similar study was reported by Smirnov et al [2007] for an important low dielectric constant ('low-κ') material, containing Si, C, O and H ('SiCOH'). These authors found that a FC passivation layer forms in the near-surface region when impacting their model dielectric film with CF x ions.…”
Section: Ion-assisted Etchingmentioning
confidence: 85%
“…27,28 Recent attempts to separate the contribution of different plasma components demonstrated the complicated nature of this phenomena. [16][17][18] For instance, a quite efficient sealing of pores in some cases can be achieved by combined effects of chemical, photochemical, and ion stimulated processes. 32,33 Some authors 27,28 reported that the plasma damage reduction can be related to removal of the degraded layer by the oxygen ions due to the high chemical sputtering rate.…”
Section: Epmentioning
confidence: 99%
“…This is the reason why significant efforts by researches are presently oriented to a separate study of VUV photons, energetic ions, and radicals impact on plasma damage of low-k materials. [15][16][17][18] Although quite significant understanding of different factors has been achieved, the studies in the references are based on special tools and instrumentations.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, computer simulation can be considered as an effective tool to give an appropriate interpretation of obtained experimental results and to reveal the mechanisms of the processes under investigation. The Monte Carlo (MC) and molecular dynamics (MD)‐based modeling were applied to study effects of the surface roughness and the presence of nanosized structural objects on the sputtering yield, and some important features of these phenomena were explained . To investigate structural changes in nanoporous materials due to ion bombardment, an atomistic approach is needed as it is necessary to analyze trajectories of all atoms, to take into account the energy deposited by incident ions and the excess energy of atoms located on pore walls as well as to consider the possibility of phase transitions caused by the fast energy release.…”
Section: Introductionmentioning
confidence: 99%